Changes in cross-strait aviation policies and their impact on tourism flows since 2009. (April 2018) - Wu, Chuntao; Jiang, Qiuyue; Yang, Hangjun
Abstract: This paper reviews the changes in cross-strait aviation policies that have occurred since 2009 and assesses the effects of those changes on tourism flows, focusing on the routes served by charter flights. This study is unique because it explores the linkage between aviation and tourism policies in a newly established market. Based on three distinct sets of time series data from 2009 to 2015, various statistics and vector autoregression methods are applied to examine the impacts of the changes on tourism as well as the relationships among scheduled services, charter services, and tourism flows. Our main findings are as follows: First, the changes have promoted scheduled services constantly and aggressively, which contributed to the transformation of cross-strait tourism into a thriving business. Second, through regulation, the changes have created a policy framework for charter flight business. Third, charter flights have become a supplement to scheduled flights in the tourism market. Our contribution is threefold. First, our study contributes to the literature on the effect of aviation policy regimes on the tourism market with respect to charter operations. Second, it provides practical guidance for regions with similar situations, such as the Korean Peninsula. Third, it has crucial policy implications for regulators and governments and provides advice for airlines in the cross-strait market. Highlights: We review the cross-strait aviation policy change process since 2009. We assess the effects of aviation policy changes on cross-strait tourism. It explores the linkage between aviation and tourism policies in a new market. The relationships among scheduled services, charters, and tourism are examined. It contributes to the literature of aviation policy on tourism in respect to charters.